The Effectiveness of QR Fact Learning Based Posters in Journalism Learning to Improve Fact Verification Skills in the Post Truth Era - Khairunisa Hasanah; Andini Nur Bahri (Suluah Pasaman, 2026)
The advancement of digital technology and the widespread use of social media in the post-truth era have blurred the boundaries between fact and opinion, increasing the spread of hoaxes, misinformation, and disinformation. This situation requires journalism students to have critical thinking skills and fact-verification skills. However, learning in higher education is still limited in providing applicable and integrated learning experiences. This study aims to measure the effectiveness of QR-Fact Learning media in improving the fact-verification skills and understanding of students in the Islamic Communication and Broadcasting Study Program (KPI). The study used the Research and Development (R&D) method with the ADDIE model. Participants consisted of 60 KPI students of UIN North Sumatra who were selected through a purposive sampling technique. The research instrument was a questionnaire whose validity and reliability had been tested, as well as pre-test and post-test. The results of the validity test showed that all instrument items were valid (r count > 0.254), while the reliability test obtained a Cronbach's Alpha value of 0.81, which is categorized as reliable. Effectiveness analysis using the N-Gain test resulted in a score of 78%, categorized as effective. The findings indicate that QR-Fact Learning media is able to improve fact-verification skills. This media is worthy of being an innovative learning alternative to strengthen information literacy and face information challenges in the digital era.